Egg and Dietary Cholesterol Consumption and Mortality Among Hypertensive Patients: Results From a Population-Based Nationwide Study - Wu, Fei; Zhuang, Pan; Zhang, Yiju; Zhan, Chuchu; Zhang, Yu; Jiao, Jingjing (Frontiers in Nutrition, 2021)
Background: Hypertensive patients are sensitive to the amount of dietary cholesterol intake, especially cholesterol from the whole eggs. Whether whole egg and dietary cholesterol consumption are suitable for hypertensive patients is still controversial. Aim: The objective of the study was to examine the associations of intake of eggs as well as the dietary cholesterol with total mortality in a Chinese nationwide cohort. Methods: We utilized data from the China Health and Nutrition Survey (CHNS) from the year of 1991 to 2015. Cumulative averages of egg and cholesterol intake were calculated to represent the consumption of the long-term diet of the participants in each available round of the survey. Cox regression models were employed to estimate the effects of eggs and dietary cholesterol from the different sources on mortality among hypertensive patients. Results: A total of 8,095 participants were included in the final analysis and followed up for a mean of 11.4 years. Finally, 927 cases of death were detected. After adjustment for the multivariate factors, consuming more than seven eggs per week was related to 29% lower mortality among the hypertensive patients compared with the consumers with not more than two eggs per week [hazard ratio (HR): 0.71; 95% CI: 0.59–0.85; P < 0.001]. Similarly, the egg-sourced cholesterol intake was inversely associated with mortality (P = 0.002) whereas intake of the dietary cholesterol from the non-egg sources was significantly related to the higher mortality (P < 0.001). However, total cholesterol intake was not related to mortality among hypertensive patients. Substituting eggs for an equivalent amount of non-egg-sourced protein-abundant foods was also associated with lower mortality. Conclusion: Higher consumption of eggs and egg-sourced dietary cholesterol was associated with lower mortality among the enrolled Chinese hypertensive patients but non-egg-sourced cholesterol intake was related to higher mortality. Therefore, our findings do not support the view that hypertensive patients should avoid whole egg consumption for the purpose of restricting dietary cholesterol intake.